Bayesian Beta Regression with the Bayesianbetareg R-Package (2019)
In this paper we summarize the main points of beta regression models under Bayesian perspective, including a presentation of the Bayesianbetareg R-package, used to fit the beta regression models under a Bayesian approach. Finally, beta regression models are fitted to a reading score database using, respectively, the Bayesianbetareg and betareg R-Packages for Bayesian and classic perspectives.